(untitled) (International Journal of Environmental Sciences, 2025)
Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system that often affects the visual pathway. Ocular manifestations, such as optic neuritis and diplopia, may serve as early disease indicators. Despite their clinical significance, data from the Middle East, particularly Jordan, are limited. The objective of this research paper is to determine the prevalence and nature of ocular manifestations among Jordanian MS patients and explore their demographic and clinical associations. A retrospective cross-sectional study was conducted on 409 MS patients with available demographic and clinical records. Variables included age, gender, MS subtype, age at onset, relapses, comorbidities, and ocular symptoms. Descriptive statistics summarized baseline characteristics. Prevalence was estimated using binomial tests with 95% confidence intervals (CI). Associations with categorical variables were analyzed using chi-square or Fisher’s exact tests, while continuous outcomes were assessed with t-tests or Mann–Whitney U tests, depending on distribution. Logistic regression identified independent predictors. Ocular manifestations were reported in 38% of patients (95% CI: 33.5–42.8%, p < 0.001). Patients with ocular symptoms had a significantly younger mean age at onset (26.6 vs. 32.4 years, p < 0.001). Gender (p = 0.015, Cramér’s V = 0.12) and MS subtype (p = 0.048, Cramér’s V = 0.14) were associated with ocular symptoms in univariate analysis but lost significance in multivariate models. Logistic regression confirmed younger onset age as the only independent predictor (OR 0.94, 95% CI: 0.92–0.96, p < 0.001). In conclusion, ocular manifestations are common among Jordanian MS patients, particularly those with younger disease onset. These findings emphasize the need for baseline ocular screening in MS care and call for prospective multicenter studies to validate and expand on these results.